Associação entre violência intrafamiliar e desnutrição infantil: um estudo caso-controle - Silva, Angela Cristina Dornelas da (2009)
It is estimated that in developing countries, about 30% of the population of children under 5 years of age are malnourished. According to UNICEF the causes of malnutrition include other factors besides availability of food and family violence have been cited as a risk factor for child malnutrition. In order to check whether there is an association between violence and moderate or severe malnutrition in children it was conducted a case-control study in a community of the city of Maceió, Alagoas. Cases were 65 pairs of mother malnourished child (children with moderate or severe malnutrition, aged between six and sixty months of age), attended at the Center for Nutritional Rehabilitation and Education (CREN) - Maceió, and controls were 64 pairs of mother- eutrophic child in the same age and without malnourished siblings. We used the questionnaire Brazilian version of the WorldSAFE to detect violence against women and against children and anthropometric evaluation to detect child malnutrition. Data were analyzed utilizing the chi square test and the odds ratio (OR). It was utilizaed the value of p ≤ 0.05 and confidence interval of 95%. The results showed that both severe physical violence against children by parents, and as physical violence against women by the husband or partner in the last twelve months were very high in both groups. It was higher among cases, but without statistical significance. For children, the threat of abandonment was the type of violence higher among malnourished. For mothers, the threat with a firearm was the type of violence higher among malnourished. Among the socio-demographic variables low maternal schooling (OR = 2.1, CI: 1.0 - 4.2), low paternal schooling (OR = 4.2, CI: 1.8 - 9.8), number of children (OR = 4.3, CI: 1.9 - 10), greater number of residents in the home (OR = 2.8, CI: 1.3 - 5.9) and low economic class (OR = 3.4, CI: 1.1 - 9.9) were associated with malnutrition. The study concluded that there was no association between violence and moderate or severe chronic malnutrition and that other studies are needed for a better understanding of the relationship between child malnutrition and violence.